(untitled) (Al-Academy, 2017)
The modern dramatic forms used technical works represented by going back to the primitive origins of drama which participated in establishing it. Those employments were results of philosophical thoughts through which many scholars stimulated philosophical tendencies call for miss for the past and going back to the social life through which intimate relations are interacting. The most important thing that the scholars relied on was ceremony as a social phenomenon which people gather around it through sentimental communication relate their concerns in addition to considering it as an expressive style carries artistic characteristics can be benefitted of in the dramatic show. These thoughts were represented in the performing activity of the pioneers of modern drama, those who violated the traditional construction of the shows and contributed in building their shows based on ceremonial practices which associate the body expression with dramatic dance, Antony Arto in particular, Jerzi, Grotovsky, Peter Brook and others). These employments received its echoes in the shows of the Lebanese director Waleed Awni who adopted the dancing ceremonies in constituting the picture of the show